Does Vigilance to Pain Make Individuals Experts in Facial Recognition of Pain? - Corinna Baum; Judith Kappesser; Raphaela Schneider; Stefan Lautenbacher (Pain Research and Management)
BACKGROUND: It is well known that individual factors are important in the facial recognition of pain. However, it is unclear whether vigilance to pain as a pain-related attentional mechanism is among these relevant factors.